The crimson field [videorecording (DVD)] - Norris, Hermione; Chaplin, Oona, 1986-; Rankin, Richard (PBS Distribution, 2015)
In a tented field hospital on the coast of France, doctors, nurses, and volunteers work together to heal the bodies and souls of men wounded in the trenches of WWI. The hospital is a frontier: between the battlefield and home front but also between the old rules, hierarchies, class distinctions, and a new way of thinking.